2022
DOI: 10.1039/d1na00710f
|View full text |Cite
|
Sign up to set email alerts
|

On the photostability and luminescence of dye-sensitized upconverting nanoparticles using modified IR820 dyes

Abstract: Dye sensitization is a promising route to enhance luminescence from lanthanide-doped upconverting nanoparticles (LnUCNPs) by improving the photon harvesting capability of LnUCNPs through the use of dye molecules, characterized by...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 37 publications
(79 reference statements)
0
17
0
Order By: Relevance
“…The first strategy explored was co-doping with a sensitizer ion. The incorporation of sensitizer ions into a nanomaterial represents a facile route to improved luminescence intensity with no additional synthetic steps, thus improving the potential for applications relative to more complex approaches such as dye sensitization or multishell architectures. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first strategy explored was co-doping with a sensitizer ion. The incorporation of sensitizer ions into a nanomaterial represents a facile route to improved luminescence intensity with no additional synthetic steps, thus improving the potential for applications relative to more complex approaches such as dye sensitization or multishell architectures. , …”
Section: Resultsmentioning
confidence: 99%
“…The incorporation of sensitizer ions into a nanomaterial represents a facile route to improved luminescence intensity with no additional synthetic steps, thus improving the potential for applications relative to more complex approaches such as dye sensitization or multishell architectures. 45,46 With respect to Eu 3+ -doped materials, sensitization using Gd 3+ is well established for photoluminescence. Gd 3+ has been demonstrated to sensitize Eu 3+ via quantum cutting through two sequential energy transfer events.…”
Section: Sqmentioning
confidence: 99%
“…Current research is being carried out towards improving this by taking advantage of the antenna effect, through the use of ligands capable of absorbing the LED light and transferring it to the lanthanide luminescent center. 47,48…”
Section: Lanthanides In Lighting and Displaysmentioning
confidence: 99%
“…Current research is being carried out towards improving this by taking advantage of the antenna effect, through the use of ligands capable of absorbing the LED light and transferring it to the lanthanide luminescent center. 47,48 2.3 Future perspectives on lighting and phosphors Hybrid organic-LEDs (OLEDs) based on lanthanides are surely interesting materials for applications in lighting and displays. [49][50][51] The OLEDs have almost completely replaced LEDs, due to their higher performance in terms of resolution and colour rendering.…”
Section: Lanthanides In Light-emitting Diodes (Leds)mentioning
confidence: 99%
“…[20][21][22] It has been demonstrated that the reaction with singlet oxygen is the main pathway (70%) for photobleaching of cyanine dyes. 23 To improve the photostability of cyanine dyes, three general strategies are proposed, including decreasing the reactivity of dyes toward 1 O 2 , 24,25 shortening the triplet-state lifetimes of dyes, [26][27][28][29][30] or encapsulating dyes to shield molecular oxygen. [31][32][33][34][35] However, many methods require complicated and expensive synthetic strategies, even often sacrifice some desirable photophysical properties of dyes, such as the extinction coefficient and fluorescence quantum yield.…”
Section: Introductionmentioning
confidence: 99%